Epigenetic Regulation of Individual Modules of the immunoglobulin heavy chain locus 3′ Regulatory Region - Birshtein, Barbara K. (Frontiers in Immunology, 2014)
The Igh locus undergoes an amazing array of DNA rearrangements and modifications during B cell development. During early stages, the variable region gene is constructed from constituent variable (V), diversity (D), and joining (J) segments (VDJ joining). B cells that successfully express an antibody can be activated, leading to somatic hypermutation (SHM) focused on the variable region, and class switch recombination (CSR), which substitutes downstream constant region genes for the originally used Cμ constant region gene. Many investigators, ourselves included, have sought to understand how these processes specifically target the Igh locus and avoid other loci and potential deleterious consequences of malignant transformation. Our laboratory has concentrated on a complex regulatory region (RR) that is located downstream of Cα, the most 3′ of the Igh constant region genes. The ~40 kb 3′ RR, which is predicted to serve as a downstream major regulator of the Igh locus, contains two distinct segments: an ~28 kb region comprising four enhancers, and an adjacent ~12 kb region containing multiple CTCF and Pax5 binding sites. Analysis of targeted mutations in mice by a number of investigators has concluded that the entire 3′ RR enhancer region is essential for SHM and CSR (but not for VDJ joining) and for high levels of expression of multiple isotypes. The CTCF/Pax5 binding region is a candidate for influencing VDJ joining early in B cell development and serving as a potential insulator of the Igh locus. Components of the 3′ RR are subject to a variety of epigenetic changes during B cell development, i.e., DNAse I hypersensitivity, histone modifications, and DNA methylation, in association with transcription factor binding. I propose that these changes provide a foundation by which regulatory elements in modules of the 3′ RR function by interacting with each other and with target sequences of the Igh locus.